Development and validation of clopidogrel bisulphate determination in bulk by UV spectrophotometric method - Antypenko, L.; Gladysheva, S.; Vasyuk, S.; Гладишева, Світлана Анатоліївна; Васюк, Світлана Олександрівна (My University, 2016)
A simple, rapid, sensitive and low-cost UV-spectrophotometric method has been developed for the quantification of clopidogrel bisulphate in pure substance. It was validated for linearity, range, accuracy, precision, ruggedness and robustness. The valid maximum absorbance was recorded at the 203 nm wavelength in the concentration ranges 1.0-2.6 mg/100mL of clopidogrel bisulphate in methanol solution after 15 min stirring. The limit of detection was found to be 0.59 mg/100mL, while the limit of quantification was 1.78mg/100mL. The calibration curve was linear with r2 =0.9929. The proposed technique could be successfully used for the determination of clopidogrel bisulphate in bulk in small laboratories without LC−MS spectrometer or HPLC-UV chromatograph, as well as for future pharmacokinetic studies in pharmaceutical dosage forms.
Keywords: clopidogrel bisulphate; validation; UV-spectrophotometry